Elon Musk [compact disc, unabridged] - Isaacson, Walter (Simon & Schuster Audio, 2023)
When Elon Musk was a kid in South Africa, he was regularly beaten by bullies. One day a group pushed him down some concrete steps and kicked him until his face was a swollen ball of flesh. He was in the hospital for a week. But the physical scars were minor compared to the emotional ones inflicted by his father, an engineer, rogue, and charismatic fantasist. His father's impact on his psyche would linger. He developed into a tough yet vulnerable man-child, prone to abrupt Jekyll-and-Hyde mood swings, with an exceedingly high tolerance for risk, a craving for drama, an epic sense of mission, and a maniacal intensity that was callous and at times destructive. At the beginning of 2022, after a year marked by SpaceX launching thirty-one rockets into orbit, Tesla selling a million cars, and him becoming the richest man on earth, Musk spoke ruefully about his compulsion to stir up dramas. For two years, Isaacson shadowed Musk, attended his meetings, walked his factories with him, and spent hours interviewing him, his family, friends, coworkers, and adversaries. The result is the revealing inside story, filled with amazing tales of triumphs and turmoil, that addresses the question: are the demons that drive Musk also what it takes to drive innovation and progress?